EFFECTIVENESS OF DIGITAL APPLICATION “QUIZIZZ” FOR STUDENTS’ LEARNING EVALUATION AT STMIK WIDYA CIPTA DHARMA SAMARINDA - Fajriantini, Aisyah; Ulfah Nurfadhila; Renni Mayasari (BEduManagers Journal : Borneo Educational Management and Research Journal, 2024)
This study focused on determining the effectiveness of Quizizz as digital application for evaluating students’ learning at STMIK Widya Cipta Dharma in the Informatics Engineering study program in the first semester of the 2024/2025. The research method used is descriptive quantitative. The sample in this study were 47 first semester students of Informatics Engineering study program. Data collection methods used descriptive observation and online questionnaire distribution in the form of GoogleForm. The results of this research show an increase in effectiveness when using the Quizizz digital application compared to the conventional system with the average score results of all students above 142% “strongly agree”. The challenges in using the Quizizz digital application are based on unstable internet connection and students’ readiness in preparing their fully-charged cellphones during the learning process until the learning evaluation session ended